The Development of attention : research and theory - Enns, James T. (Advances in psychology (Amsterdam, Netherlands) ;, 1990)
This volume presents an up-to-date review of developmental aspects of human attention by leading researchers and theorists. The papers included in the first section consider the ways in which newborns are pretuned to visual, auditory, linguistic, and social features of their environment, as well as how selectivity to these features changes in the first year of life. The following section examines properties of the visual and auditory world that are attention-getting for children. Developmental increases in capacity and strategy are also examined in this section through the study of perception, memory, problem-solving and language. Section III explores several ways in which selective processing can fail in development (e.g. autism, hyperactivity, and psychopathy) while Section IV reports on those aspects of selectivity that are lost (and preserved) in the aging process.